2015
DOI: 10.1130/ges01036.1
|View full text |Cite
|
Sign up to set email alerts
|

Focused rock uplift above the subduction décollement at Montague and Hinchinbrook Islands, Prince William Sound, Alaska

Abstract: Megathrust splay fault systems in accretionary prisms have been identifi ed as conduits for long-term plate motion and signifi cant coseismic slip during subduction earthquakes. These fault systems are important because of their role in generating tsunamis, but rarely are emergent above sea level where their long-term (million year) history can be studied. We present 32 apatite (U-Th)/He (AHe) and 27 apatite fi ssion-track (AFT) ages from rocks along an emergent megathrust splay fault system in the Prince Will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 97 publications
0
11
1
Order By: Relevance
“…Although the entire PWS region was uplifted in 1964, geodetic data show that central PWS has been gradually subsiding since the earthquake, consistent with a locked megathrust interface (Freymueller et al, 2008). The relatively moderate interseismic subsidence contrasts with the estimated millennial-scale exhumation rates of greater than 1 mm=yr recorded with thermochronology methods for rocks in the hanging wall of the Patton Bay megathrust splay fault (Arkle et al, 2013;Ferguson et al, 2015;Haeussler et al, 2015). Hence, coseismic uplift rates have outpaced interseismic subsidence rates in the hanging wall of these splay faults for PWS throughout the Quaternary record.…”
Section: Tectonic Setting and Earthquake Historymentioning
confidence: 72%
See 1 more Smart Citation
“…Although the entire PWS region was uplifted in 1964, geodetic data show that central PWS has been gradually subsiding since the earthquake, consistent with a locked megathrust interface (Freymueller et al, 2008). The relatively moderate interseismic subsidence contrasts with the estimated millennial-scale exhumation rates of greater than 1 mm=yr recorded with thermochronology methods for rocks in the hanging wall of the Patton Bay megathrust splay fault (Arkle et al, 2013;Ferguson et al, 2015;Haeussler et al, 2015). Hence, coseismic uplift rates have outpaced interseismic subsidence rates in the hanging wall of these splay faults for PWS throughout the Quaternary record.…”
Section: Tectonic Setting and Earthquake Historymentioning
confidence: 72%
“…Open circles in (a) and (c) represent island-based seismic stations used for refraction models (Brocher et al, 1994). Ferguson et al, 2015;Haeussler et al, 2015). To the west of the Smith Islands, there is no evidence from seismic profiling or seafloor bathymetry for along-strike uplift (Liberty, 2013).…”
Section: Central Pws Active Faultsmentioning
confidence: 99%
“…In addition, the large coseismic slip area between the Kenai Peninsula and the Montague Island shows a localized low‐Vs and high‐ν anomaly in the overriding plate. Focused and rapid exhumation has taken place around the Montague Island as revealed by young apatite (U‐Th)/He ages of <5 Ma, especially in the southwestern island (Arkle et al, ; Ferguson et al, ; Valentino et al, ). Haeussler et al () suggested that several splay faults there have accommodated the exhumation and rooted into the megathrust where there is probably underplating.…”
Section: Discussionmentioning
confidence: 99%
“…Surface ruptures during subduction zone earthquakes can highlight patterns of coseismic motion (e.g., Fujiwara et al, 2011;Henstock et al, 2006), paleoseismic and geodetic observations can provide estimates of recurrence intervals and patterns of uplift/subsidence (e.g., Atwater & Hemphill-Haley, 1997;Cisternas et al, 2005;Saillard et al, 2017;Shennan et al, 2014;Sieh et al, 2008), and thermochronology measurements can provide regional uplift rates over thousands of earthquake cycles (e.g., Enkelmann et al, 2015;Ferguson et al, 2015;Haeussler et al, 2015). Surface ruptures during subduction zone earthquakes can highlight patterns of coseismic motion (e.g., Fujiwara et al, 2011;Henstock et al, 2006), paleoseismic and geodetic observations can provide estimates of recurrence intervals and patterns of uplift/subsidence (e.g., Atwater & Hemphill-Haley, 1997;Cisternas et al, 2005;Saillard et al, 2017;Shennan et al, 2014;Sieh et al, 2008), and thermochronology measurements can provide regional uplift rates over thousands of earthquake cycles (e.g., Enkelmann et al, 2015;Ferguson et al, 2015;Haeussler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thrust faults that splay from a megathrust within subduction zone accretionary wedges can pose major seismic and tsunami hazards, yet little is known about the spatial and temporal controls on this family of faults. Surface ruptures during subduction zone earthquakes can highlight patterns of coseismic motion (e.g., Fujiwara et al, 2011;Henstock et al, 2006), paleoseismic and geodetic observations can provide estimates of recurrence intervals and patterns of uplift/subsidence (e.g., Atwater & Hemphill-Haley, 1997;Cisternas et al, 2005;Saillard et al, 2017;Shennan et al, 2014;Sieh et al, 2008), and thermochronology measurements can provide regional uplift rates over thousands of earthquake cycles (e.g., Enkelmann et al, 2015;Ferguson et al, 2015;Haeussler et al, 2015). However, detailed slip partitioning and uplift patterns over multiple earthquake cycles remains unknown.…”
Section: Introductionmentioning
confidence: 99%